Internalization Strategy of Religious Moderation Values Based on Pesantren Local Content Curriculum - Rohmaniah, Siti; Bustomi, Ahmad; Zulihi, Zulihi (Nizham Jurnal Studi Keislaman, 2024)
The purpose of this study is to analyze the strategy of internalizing religious moderation values carried out through the curriculum of local content of pesantren at the Bustanul Ulum Islamic Boarding School in Central Lampung. Researchers use qualitative research and the type of research used field research. Researchers use two data sources, namely primary data sources and secondary data sources. The primary data sources that will be used as material for this study include key persons who include: Cottage caregivers, leaders of madrasah institutions at Bustanul Úlum Islamic Boarding School while the skunder data used in this study are supporting data derived from books, articles, journals, e-books, and information relevant to the title that the author is researching. Data collection techniques use observation, interview, and documentation techniques with data analysis consisting of data collection, data reduction, data presentation, and conclusions. Researchers use triangulation techniques in checking data. Triangulation is the process of collecting and analyzing data through a multi-method approach. The results showed that there were at least two strategies that researchers found in implementing moderation values, namely first, Strengthening Moderation Values through Student Activities. Second, strengthening socio-cultural values with community service activities.